Pengaruh Employee Engagement Dan Kepuasan Kerja Terhdap Kinerja Pegawai Dinas Kependudukan Dan Pencatatan Sipil Di Toraja - Debianty P. Amping; Adriana M Marampa; Rahma G.Tammu (Prosiding Seminar Nasional Manajemen dan Ekonomi, 2023)
The study aims to determine the effect of employee engagement and job satisfaction on employee performance population and civil registration service in Toraja. The object of this research is population and civil registration service in Toraja. This study uses a quantitative approach with multiple linear regression analysis,to test and prove the research hypothesis using the SPSS version 22 application. The population in this study is government employees population and civil registration service in Toraja as many as 44 respondents. Research shows that Employee Engagement and Job Satisfaction together have a positive and significant effect on performance. By testing the coefficient of determination, a value of 0,433 is obtained, which means 43,3%. Performance variables can be explained by the variables Employee Engagement and Job Satisfaction while the remaining 56,7% is explained by other variables.